Financial Liberalization and the Changing Characteristics of Nordic Stock Returns - Birger Nilsson (Lund University, School of Economics and Management, Department of Economics, 2002)
This paper uses a multivariate regime-switching framework to investigate and endogenously date changes in return characteristics on the four largest Nordic stock markets. We find that the deregulated time-period, specifically after 1982, is associated with higher expected return, higher volatility, stronger links with international stock markets and higher correlation between the Nordic stock markets. This higher correlation is mainly driven by common higher correlation with international stock returns and not by higher correlation between country specific components of return. Further, our evidence support the argument that market liberalization creates excess volatility but also that Nordic investors are more than compensated for this by higher expected returns and the opportunity to cross-border diversification after liberalization.
Keywords: C15; F36; G15; G18; 330; stock market liberalization; excess volatility; portfolio diversification; multivariate regime-switching models; simulated annealing